Financial Reporting of Mosques under ISAK 35: Transparency and Accountability in Nonprofits - Caniago, Nicholas; Susanti, Septria (El-Rusyd, 2026)
As nonprofit organizations, mosques have a responsibility to present transparent and accountable financial statements to their congregants and donors. However, many mosques still prepare financial statements in a rudimentary manner and do not adhere to applicable accounting standards. This study aims to analyze the application of ISAK 35 in the presentation of financial statements at a mosque in Indonesia. The study employed a descriptive qualitative method, using primary data sources such as interviews and secondary data sources such as financial statements, transaction records, and a list of the mosque’s fixed assets. Data collection was conducted through interviews and documentation, while data analysis involved reconstructing the financial statements in accordance with ISAK 35 provisions. The results indicate that the financial statements of the Jami’ Pauh Mosque are still prepared in a simplified manner and include only revenues and expenses. This presentation does not yet meet the requirements of ISAK 35 because it does not include a statement of financial position, a statement of comprehensive income, a statement of changes in net assets, and a statement of cash flows. After reconstruction based on ISAK 35, the following figures were obtained: a statement of financial position of Rp 4,053,488,666.67; a comprehensive income deficit of Rp 95,388.89; net assets of Rp 4,053,488,666.67; and a cash flow balance of Rp 4,921,500.00. These findings highlight the importance of improving the accounting skills of mosque administrators so they can apply appropriate financial reporting standards.